Academic integrity in the HyFlex learning environment. Issue 2 (February 2023) - Eshet, Yovav; Dickman, Nomy; Ben Zion, Yossi
Abstract: This study analyzed how students' personality traits and course attendance preferences impact academic integrity in the HyFlex learning environment. 535 undergraduate students were given a choice among courses face-to-face (F2F), online, or a hybrid combination of both. The Big Five Inventory and the Academic Integrity Inventory were administered through online questionnaires to STEM students. The findings show that emotional stability and agreeableness positively relate to academic integrity irrespective of attendance mode. So do conscientiousness and agreeableness in the hybrid environment. Conversely, the primarily F2F attendance mode and the personality trait of extraversion are tied to markedly low levels of academic integrity. We conclude that unveiling students' personality traits associated with ethical behaviour would be beneficial when designing HyFlex courses in different learning environments, whether human (F2F), machine-made (online) or a combination of both (hybrid). This, in turn, contributes to better higher quality education and enhances academic integrity.